Reklama w przestrzeni miasta – wybrane kwestie "widzialności billboardów" - Jakiel, Małgorzata (Uniwersytet Wrocławski. Wydział, Prawa, Administracji i Ekonomii, 2013)
The article focuses on the topic of advertisements in the city. Its main concern is billboards’ location and their perception by people. The concept of space is relevant to the topic as specific location of billboards influences their significance for recipients. Also, since development of cities is a consequence of human and non-human relations and interactions, the presence of billboards is one of the most integral part of this process.
Keywords: reklama; Wrocław; miasto; billboardy